Thrush nightingales adjust the peak frequency and structure of their songs in response to different types of experimental noise - Michał Budka (Scientific Reports)
Abstract Animals employ various strategies to minimize the overlap of their vocalizations with other sounds, thereby enhancing the effectiveness of their communication. However, little attention has been given to experimentally examining how the structure of the acoustic signal changes in response to various kinds of disturbances in the soundscape. In this study, I experimentally investigated whether male thrush nightingales (Luscinia luscinia) adjust their singing rate, song frequency, and song type in response to different types of artificial sounds. While males did not reduce the intensity of their singing in noise, they did adjust the peak frequency of their songs—raising it in the presence of low-frequency noise and lowering it in response to high-frequency noise. These bidirectional changes were associated with selective use of phrases from their repertoire. The proportion of low- to high-frequency phrases was significantly reduced under low-frequency noise and increased under high-frequency noise. The results suggest that disturbing sounds can modify the peak frequency and structure of songbird vocalizations, at least in the short term. Birds may enhance the signal-to-noise ratio by selecting phrases from their repertoire that are less affected by noise. For species with a large repertoire, new sounds transmitted within a species-specific frequency range may play an important role in the process of cultural song transmission.